HIV/AIDS and Substance Use Prevention for African American Young Adults: Field Evaluation of "Color it Real". (May 2021) - Agley, Jon; Xiao, Yunyu; Jayawardene, Wasantha; Gay, Albert; King, Rosemary; Horne, Kelly; Walker, Roland
In the United States, African Americans continue to bear a disproportionate amount of risk from HIV and illicit drug use, highlighting the importance of culturally responsive prevention programming. Manualized HIV and substance use prevention curricula that are conceptually African centered are few, and evaluative data of such programs are sparse. This research brief aims to describe a field evaluation of the "Color it Real" (CIR) program, a 6-session, 12-hr HIV and substance use prevention curriculum for African American males and females aged 18 to 24 years. Participants ( n = 225) were recruited using convenience sampling from two cities within a high-risk county in Indiana. Attitudes, knowledge, and confidence related to HIV and substance use were assessed before and after the intervention. Wilcoxon and McNemar tests were used to compare pretest and posttest scores, and binary logistic regression models were used to examine sociodemographic associations with outcomes. Among the analytic sample ( n = 195), the CIR program was associated with several improved attitudes and increased knowledge related to HIV and substance use, but not with increased confidence in sexual negotiation skills. These findings represent the first published data from CIR since the developers' original study, and support continued use of the curriculum by our program. Given the positive findings (i.e., attitudes and knowledge) and community receptiveness to CIR, we believe that a randomized, controlled trial of the intervention that includes longitudinal behavioral measurement would be a meaningful addition to prevention research.